PENGARUH TINGKAT KUALITAS CORPORATE GOVERNANCE TERHADAP RISK-TAKING PERUSAHAAN - Muhammad Fadhlal Maula, Nasir (Departemen Manajemen, 2017)
This research examines about the effect of corporate governance quality level to corporate risk-taking. On the research, there are one independent variable that is Corporate Governance Perception Index and one dependent variable that is corporate risk-taking which is measured by systematic risks and non-systematic risks. The sample of this research was taken from all companies listed on Indonesia Stock Exchange and also included in the rank of The Indonesian Institute for Corporate Governance (IICG) on 2011-2013. The sample were taken by purposive sampling method. Total sample that were used are 13 corporates with total observation data are 39. Statistical methods using simple linear regression analysis were used to test the hypothesis. The result of this research indicates that the level of corporate governance quality has a negative impact significantly to corporate risk-taking as measured by systematic risk or non-systematic risk. Company with good level of corporate quality will make a small risk decisions. Keywords: Corporate Governance, Corporate Governance Perception Index, RiskTaking, Agenchy Theory